Interference of cold agglutinin autoantibodies in erythrogram interpretation: a case report and literature review - Bruno Miguel B. Costa; Maria C. Vellés; Maria Mariana F. B. Viana; Catarina Isabel M. Rebelo (Sociedade Brasileira de Patologia Clínica, 2018)
ABSTRACT The erythrogram is one of the components of the blood count that includes red blood cell (RBC) quantification and evaluation. A correct interpretation and validation of the results obtained in an erythrogram require experience and critical awareness of health professionals. It is imperative to evaluate the interference of physiological variables, collection procedures, manipulation of samples and endogenous variables (such as the presence of cold agglutinin autoantibodies), since these may falsify the results obtained. Cold agglutinin autoantibodies are predominantly immunoglobulin type M (IgM), which cause agglutination of RBC at temperatures below 37°C, and may appear in cases of autoimmune hemolytic anemia and atypical pneumonia, among other pathologies. The presence of erythrocyte agglutination interferes with RBC and reticulocyte counts, determination of the globular volume and the blood count indices. A set of laboratorial procedures may be performed in order to eliminate the interference of these agglutinins in the results of the erythrogram. If these procedures do not correct the values obtained, the only result of the erythrogram that can be validated is hemoglobin, since the remaining results are falsified due to the presence of cold agglutinin autoantibodies.